Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Karyawan Terminal Kargo Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Erlyn Herliana; Arif Fakhrudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Compensation is the imbalance received by employees regarding the work output of employees in the company, both physical and non-physical compensation given to employees in accordance with their sacrifices for the company. Motivation is one of the factors that encourages a person to carry out a certain activity, therefore motivation is often interpreted as a factor that drives a person's behavior. The purpose of this research is to determine the effect of compensation on the performance of cargo terminal employees at General Ahmad Yani Semarang International Airport, to determine the effect of motivation on the performance of cargo terminal employees at General Ahmad Yani Semarang International Airport, to determine the simultaneous influence of compensation and motivation on the performance of terminal employees General Ahmad Yani Semarang International Airport cargo, to find out how much influence compensation and motivation have on the performance of General Ahmad Yani Semarang International Airport cargo terminal employees. This type of research uses quantitative methods, the population used is employees of the cargo terminal at Ahmad Yani Airport, Semarang. The sample used a probability sampling technique in the form of random sampling with 50 samples. The conclusion obtained by the research is that the compensation variable does not have a major influence on the performance of cargo terminal employees, while motivation has an influence on the performance of cargo terminal employees, as evidenced by the results of the calculated T compensation test of -2,300 and the calculated T motivation of 5,954.